2011
DOI: 10.1002/cphc.201100671
|View full text |Cite
|
Sign up to set email alerts
|

Optical Modulation and Selective Recovery of Cy5 Fluorescence

Abstract: Fluorescence modulation offers the opportunity to detect low concentration fluorophore signals within high background. Applicable from the single molecule to bulk levels, we demonstrate long-wavelength optical depopulation of dark states that otherwise limit Cy5 fluorescence intensity. By modulated excitation of a long wavelength Cy5 transient absorption, we dynamically modulate Cy5 emission. The frequency dependence enables specificaton of the dark state timescales enabling optical demodulation-based signal r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
57
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(57 citation statements)
references
References 55 publications
(89 reference statements)
0
57
0
Order By: Relevance
“…Excitation of cis-Cy5 in its absorption band, however, photoreverts the Cy5 to the trans state and recovers fluorescence with enhancements of up to 50%. 18 Although Cy5 excitation also shows triplet state dynamics for both trans- and cis-isomers, the T 1 levels have much shorter lifetimes of ~35 μs and 6 μs for the trans and cis isomers, respectively. 16 Thus, our approach of fluorescence excitation combined with secondary laser co-illumination that is on-resonance with the transient absorption dynamically modulates the Cy5 fluorescence intensity via optical depopulation of primarily the photoisomerized dark state.…”
Section: Introductionmentioning
confidence: 99%
“…Excitation of cis-Cy5 in its absorption band, however, photoreverts the Cy5 to the trans state and recovers fluorescence with enhancements of up to 50%. 18 Although Cy5 excitation also shows triplet state dynamics for both trans- and cis-isomers, the T 1 levels have much shorter lifetimes of ~35 μs and 6 μs for the trans and cis isomers, respectively. 16 Thus, our approach of fluorescence excitation combined with secondary laser co-illumination that is on-resonance with the transient absorption dynamically modulates the Cy5 fluorescence intensity via optical depopulation of primarily the photoisomerized dark state.…”
Section: Introductionmentioning
confidence: 99%
“…The modulation frequency dependence has been shown to be indicative of the natural dark state lifetime. 20 Because the secondary laser was square wave modulated at 100 Hz, Cy5 fluorescence was also modulated at 100 Hz, as revealed by Fourier transformation of the fluorescence intensity (Figure 5A–B). As Texas red fluorescence is not modulatable, demodulated fluorescence signals are indicative of only Cy5 emission and are directly recoverable even when buried up to 6 mm deep within skin tissue phantoms (Figure 5B).…”
Section: Resultsmentioning
confidence: 99%
“…Secondary illumination, however, only depopulates the primary laser-prepared dark state of Cy5 without modulating Texas red emission. 20 Texas Red is more efficiently excited at 594nm than is Cy5, somewhat offsetting the better spectral match of the filter passband to the Cy5 emission. Regardless, ~25% of Texas Red and ~75% of Cy5 emission is collected in the collected spectral region.…”
Section: Experimental and Computational Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have shown that this amplitude scales linearly with the total number of modulatable molecules and is shifted to its own unique detection frequency, free from obscuring background signals. 910, 14, 21, 25 While this amplitude is linear in the number of molecules, the slope of Fourier amplitude vs. concentration of modulatable species is a product of many photophysical and experimental parameters. Thus, accurate numbers of molecules can only be obtained from the Fourier amplitude if calibrated by the correlation subtracted SAFIRe-FCS or through a predetermined calibration curve obtained under identical conditions.…”
Section: Safire-fcsmentioning
confidence: 99%